История кафедры славянской филологии Вильнюсского университета - Михайловна Коницкая, Елена (Slavistica Vilnensis, 2009)
The article provides an overview of the history of the Department of Slavic Philology, the foundation of which as part of the Philology Faculty at Vilnius University was laid by professor V. N. Čekmonas in spring 1987. The article reviews the development of academic and scientific programs throughout the twentyyear history of the department, the training of professionals in various Slavic languages and cultures, as well as the growth of scientific manpower. Since its inception, the Department has prepared professionals in West and South-Slavic languages, developed unique educational studies, created the region’s largest library of scientific and educational literature, and trained interpreters in Czech, Bulgarian, Serbian, Croatian, and Slovenian. Innovative activities have lead to the introduction of Hungarian and Turkish languages at the department, so the teaching of these languages has become one more activity of the department. Special attention is paid to scholarly research, fostering of international contacts, and practical activities of the departamental staff and graduates.